A Comparative Analytical Study Of Consumer Price Indices Among The Syrian Governorates During The Period 2011-2018 - صقر, محمد; عقول, منار (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aimed to study the changes that occurred in the consumer price index according to each governorate and its development over time, and then study the variation between the Syrian governorates in the index numbers during the period 2010-2018. The researcher relied on the historical approach by adopting a period of time extending from 2010 to 2018, studying it, and knowing its direction and growth. The researcher also followed a descriptive approach that relies on collecting data and information that helps to accurately describe the problem, and analyze it to reach accurate results. The results showed that the general trend line for the evolution of the consumer price index in the Syrian governorates is taking an increasing trend with time except for the year 2014, as the changes brought about by the war factors during the study period greatly affected the rise in the general level of prices. The results also showed that there is homogeneity in the consumer price index among the Syrian governorates, in terms of the absence of a statistically significant difference between the Syrian governorates in the rates of consumer price indices.